2010
DOI: 10.5551/jat.3624
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Renin-Angiotensin System Attenuates Advanced Glycation End Products-Mediated Signaling Pathways

Abstract: Aim: Advanced glycation end products (AGE) and a receptor for AGE (RAGE) play a key role in diabetic vascular complications. Matrix metalloproteinases (MMPs) and apoptosis contribute to plaque instability. The renin-angiotensin system (RAS) is crucial for NADPH oxidase-dependent redox signaling pathways in the vascular wall. We investigated the effects of RAS blockade on AGE-triggered signaling pathways and its downstream events, including MMP-9 and apoptosis. Methods: We used cultured rabbit aortic smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 51 publications
(46 reference statements)
2
25
0
1
Order By: Relevance
“…RNH-6270 showed no ef- fect on the electron paramagnetic resonance signals of the DMPO/superoxide spin adduct [14]. Kamioka et al [21] also reported that olmesartan inhibited ROS production by advanced glycation end products via inhibition of NADPH oxidase activity. TNF-α-induced ROS production is also mediated by NADPH oxidase acitivation [22].…”
Section: Discussionmentioning
confidence: 94%
“…RNH-6270 showed no ef- fect on the electron paramagnetic resonance signals of the DMPO/superoxide spin adduct [14]. Kamioka et al [21] also reported that olmesartan inhibited ROS production by advanced glycation end products via inhibition of NADPH oxidase activity. TNF-α-induced ROS production is also mediated by NADPH oxidase acitivation [22].…”
Section: Discussionmentioning
confidence: 94%
“…Several currently available pharmacologic agents may regulate esRAGE or sRAGE. Inhibitors of angiotensin-converting enzyme (ACE) increase renal expression of sRAGE in rats, and this is associated with decreases in the expression of RAGE (28). ACE inhibition in diabetic rats and in humans with type 1 diabetes significantly increases sRAGE concentrations (28).…”
Section: Rage the Biology Of Rage Is Summarized Inmentioning
confidence: 99%
“…Indeed, clinical drugs inhibiting the Nox4/ROS-NF-κB pathway can be used in the treatment and/or prevention of atherosclerosis. For example, angiotensin-converting enzyme inhibitors, such as temocaprilat, or angiotensin Ⅱ receptor antagonists, such as olmesartan, not only inhibit the NADPH oxidase activity, including the p22phox expression, but also NF-κB activation, which induces the generation of ROS 41,42) . Statins also inhibit the NAPDH oxidase activity 43,44) and the activation of various related downstream signaling pathways, including that of p38 and ERK1/2, in order to produce anti-atherosclerotic effects 14,45) .…”
Section: Discussionmentioning
confidence: 99%